Keputusan Konsumen Dalam Pembelian Sayuran Di Pasar Bahu Kecamatan Malalayang Kota Manado - Simbolon, Velin; Mandei, Juliana Ruth; Jocom, Sherly Gladys (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to describe the factors that determine vegetable purchasing decisions at Bahu Market, Malalayang District, Manado City. The research employs a descriptive analysis method. The collected data are described and qualitatively analyzed, presented in tabular form, and explained descriptively. Based on the results of the research, the factors determining vegetable purchasing decisions at Bahu Market, Malalayang District, Manado City, are ranked as follows: the highest is Attitude, followed by Lifestyle, Price, Quality, and the lowest is Location. Consumer attitude is the primary determining factor in vegetable purchasing decisions.